Barriere e facilitatori inerenti all’applicazione dell’evidence-based nursing: una revisione della letteratura. - Paglialonga, Paolo; Vitiello, Antonio; Balestreri, Elisabetta; Frontuto, Vittoria (Italian Journal of Nursing (IJN) / Giornale Italiano di Infermieristica, 2025)
Background During Bachelor of Science in Nursing program education, student nurses are introduced to evidence-based practice (EBP), but although its benefits on care are known, this approach is not constantly used in professional practice environment. The literature reports numerous factors that hinder/facilitate its implementation. Objective To investigate the main barriers and elements facilitating EBP among nurses and nursing students. Methods A review of the literature was conducted on PubMed, Cochrane Library, ILISI, consulting gray literature (degree theses in nursing of the University of Milan). The studies were then summarized using a narrative approach. Results The review included 50 studies; 12 barrier elements have been identified: work overload, lack of EBP skills and inadequate facilities are the most frequent. Furthermore, 13 different facilitators were identified, among which training events, organizational support and educational level are the most frequent types. Conclusions Most of the barriers and facilitators identified can be influenced by the managers of health care professionals. Specifically, training interventions would appear to be particularly effective, but there are no studies that highlight the best methodology for EBP training. Furthermore, the need for an increase in studies in the Italian context is evident, as it presents particular complexities compared to the rest of the world. This study constitutes strategic support for managers who intend to promote the diffusion of evidence-based treatment.